Study of management of supracondylar femoral fracture using dynamic condylar screw - Mohan, Lalith; Benguluri, Ramesh (International Journal of Research in Orthopaedics, 2019)
Background: Supracondylar femoral fracture poses a considerable therapeutic challenge. Operative treatment has become a standardized procedure. Stabilization has usually been achieved by an osteosynthesis with dynamic condylar screws or retrograde supracondylar nailing. In this article we are going to compare the results of surgical management of supracondylar nail and dynamic condylar screw. The aim is to study the effectiveness of dynamic condylar screw in surgical management of supracondylar fractures of femur. Methods: Prospective study of patients who had sustained supracondylar fracture of femur. The patients included in this study were those with supracondylar fractures of the femur with or without articular involvement and disruption of the joint surface. Study was done for a period of two and half years. Results: In our study of 21 cases, there were 8 patients (38%) who had associated fractures. Two patients were more than 50 yrs. 3 patients had compound injury which were grade-II of Gustilo Anderson classification. One of them developed post-operative infection and resulted in poor outcome. Other 2 patients had decrease range of movements resulted in fair outcome. Type C2 constituted highest number 8 (38%) followed by type A3 which was 28.5% i.e., 8 patients. Infection is observed in 9.5% of patients. 2 patients had implant failure and both were due to early weight bearing. In our study excellent and good results were found to be in 61.9%. Conclusions: Role of dynamic compression screw in the surgical management of supracondylar fractures of the femur minimizes the risk of complications.